(untitled) (Revista revoluciones, 2023)
There is little research on personality traits in women for and against abortion. The present study aimed to determine the differences in personality traits between women for and against abortion. A quantitative, descriptive-comparative, cross-sectional methodological design was used. We worked with a sample of 30 women selected through a non-probabilistic convenience sampling, to whom the following instruments were applied: Socio-demographic questionnaire, Reasoning about abortion questionnaire (RAQ) likert scale and the Eysenk personality inventory. The results were analyzed using descriptive statistics in Excel, which allowed us to conclude that there were no significant differences in personality traits in the groups of women studied.